Changes in Use of a Leisure Activity Mobile App for Children With Disabilities During the COVID-19 Pandemic: Retrospective Study - Paul Yejong Yoo; Mehrnoosh Movahed; Ishana Rue; Carlos Denner Dos Santos; Annette Majnemer; Keiko Shikako (JMIR Publications, 2022)
BackgroundParticipation in leisure activities is essential for child development and a human right as per the United Nations Convention on the Rights of the Child. Children with disabilities face several restrictions when participating in leisure activities as compared to same age peers without disabilities. Access to information about accessible, inclusive leisure activities is one of the barriers limiting participation, and one potential health promotion strategy is to provide access to information to increase participation. The Jooay App is a mobile app listing such activities in Canada and Australia. With the COVID-19 global pandemic and subsequent public health measures, most community-based facilities providing the activities listed on Jooay were closed. The app therefore started listing online activities offered with the expectation of continuing to provide information for families and understanding the extent to which users relied on the mobile app as a tool to identify new safe leisure opportunities. ObjectiveThis study aims to describe the engagement of the Jooay app before and during COVID-19, and to estimate the extent to which the listing of online activities was related to the engagement of the Jooay app. MethodsWe conducted a retrospective study comparing Jooay app use between March 2020 and February 2021 to the engagement between March 2019 and February 2020 by Jooay users. Spearman rank correlations were carried out to identify associations between the activities listed and the users' engagement from May 2020 to February 2021. ResultsActive engagement with the Jooay app from March 2020 to February 2021 dropped by an average of 135 engagements (64.2%) compared to engagements in 2019-2020. The largest monthly drop in engagement was observed in May 2020 by 239 engagements (88.8%). There was a strong positive correlation between the number of active users and the number of online activities listed on the app (rs=0.900). ConclusionsThe engagement with the Jooay App presented an expected decrease during the first wave of the COVID-19 pandemic. The addition of online adapted leisure activities to the app's listings during the pandemic increased app use. Access to information about inclusive activities is a barrier for children with disabilities to engage in leisure. Mobile health solutions can be responsive to contextual factors and consider the social determinants of health such as socioeconomic and public health emergency issues that can impact the participation of vulnerable populations such as children with disabilities and help eliminate barriers to participation. The provision of online leisure opportunities during the pandemic could facilitate participation in these activities during the pandemic and beyond, which is essential and beneficial for the physical and mental well-being of children with disabilities and their families.